Nitrogen Transport/Deposition from Paddy Ecosystem and Potential Pollution Risk Period in Southwest China - Guo, Shufang; Yan, Tiezhu; Zhai, Limei; Yen, Haw; Liu, Jian; Li, Wenchao; Liu, Hongbin (Water (Basel), 2022)
Nitrogen (N) losses through runoff from cropland and atmospheric deposition contributed by agricultural NH3 volatilization are important contributors to lake eutrophication and receive wide attention. Studies on the N runoff and atmospheric N deposition from the paddy ecosystem and how the agriculture-derived N deposition was related to NH3 volatilization were conducted in the paddy ecosystem in the Erhai Lake Watershed in southwest China. The critical period (CP) with a relatively high total N (TN) and NH4+-N deposition occurred in the fertilization period and continued one week after the completion of fertilizer application, and the CP period for N loss through surface runoff was one week longer than that for deposition. Especially, the mean depositions of NH4+-N in the CP period were substantially higher than those in the subsequent period (p < 0.01). Moreover, agriculture-derived NH4+ contributed more than 54% of the total NH4+-N deposition in the CP period, being positively related to NH3 volatilization from cropland soil (p < 0.05). The N concentrations were higher in the outlet water of ditches and runoff in May than in other months due to fertilization and irrigation. Therefore, to reduce the agricultural N losses and improve lake water quality, it is important to both reduce agricultural NH4+-N deposition from NH3 volatilization and intercept water flow from the paddy fields into drainage ditches during the CP.